Jatropha curcas: Plant of Medical Benefits - Reddy Prasad, D. M.; Amirah, Izam; Khan, Maksudur R. (Academic Journals, 2012)
Plants are a rich source of many natural products most of which have been extensively used for human welfare, and treatment of various diseases. Jatropha curcas, a multipurpose, drought resistant, perennial plant belonging to Euphorbiaceae family is gaining a lot of economic importance because of its several potentials in industrial application and medicinal values. J. curcas has been used as traditional medicine to cure various infections. Researchers had isolated and characterized numerous biologically active compounds from all parts of this plant. In addition, the mechanisms of action of these active compounds have been studied in relation to the applications in traditional medicine. Before exploiting any plant for medicinal application, it is crucial to have complete information about the medicinal uses of each part of the plant. The medicinal uses of the leaves, fruit, seed, stem bark, branches, twigs, latex and root of J. curcas are discussed in this review. If the full potential of the plant is to be revealed, much more research is required to develop herbal medicine using modern science and technology. A potential aspect based on markets for all of its medicinal products should be conducted thoroughly, to promote the ability of this plant to cure so many illnesses.